2007
DOI: 10.4049/jimmunol.179.4.2551
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Receptor Accessory Protein and ST2 Comprise the IL-33 Receptor Complex

Abstract: IL-33 (IL-1F11) is a recently described member of the IL-1 family of cytokines that stimulates the generation of cells, cytokines, and Igs characteristic of a type 2 immune response. IL-33 mediates signal transduction through ST2, a receptor expressed on Th2 and mast cells. In this study, we demonstrate that IL-33 and ST2 form a complex with IL-1R accessory protein (IL-1RAcP), a signaling receptor subunit that is also a member of the IL-1R complex. Additionally, IL-1RAcP is required for IL-33-induced in vivo e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
369
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(398 citation statements)
references
References 23 publications
7
369
0
14
Order By: Relevance
“…IL-33 is produced as a 30 kDa protein. After binding to the long form of the ST2 receptor (ST2L), IL-33 recruits IL-1RAcP, the common co-receptor for IL-1α and IL-1β, to activate signaling pathways, including NF-κB and MAP kinases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 is produced as a 30 kDa protein. After binding to the long form of the ST2 receptor (ST2L), IL-33 recruits IL-1RAcP, the common co-receptor for IL-1α and IL-1β, to activate signaling pathways, including NF-κB and MAP kinases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…ST2 is expressed on mast cells (18), LPS-activated macrophages (7), and Th2 lymphocytes (19) and exists as transmembrane (ST2L) and soluble (sST2) isoforms generated by alternative splicing (20). IL-33 has been shown to induce the secretion of both proinflammatory and antiinflammatory cytokines and chemokines from mast cells, eosinophils, and Th2 lymphocytes (16,21,22). However, the influence of IL-33 on macrophages has not yet been studied.…”
mentioning
confidence: 99%
“…These molecules are shared by other TLR-dependent pathways, notably the CD14/MD2/TLR-4 complex, which is triggered by LPS. Recently, the IL-1R accessory protein IL-1RAcP, which is also involved in IL-1 signaling, was found to heterodimerize with ST2 when IL-33 is bound to ST2 (16,17). ST2 is expressed on mast cells (18), LPS-activated macrophages (7), and Th2 lymphocytes (19) and exists as transmembrane (ST2L) and soluble (sST2) isoforms generated by alternative splicing (20).…”
mentioning
confidence: 99%
“…It is found in various cells included fibroblasts, bronchial and epithelial cells, endothelial cells, and some immune cells, including macrophages and dendritic cells (Kakkar and Lee 2008). IL-33 is a multifunctional cytokine in immune regulation that activates Th1 cells, Th2 cells, CD8+T cells and NK cells (Chackerian et al, 2007;Bourgeois et al, 2009;Liew, et al, 2010;Bonilla et al, 2012). Accumulated data also demonstrated that immune cells play important role in tumor progress and prognosis (Dobrzanski et al, 2006;Williams and Bevan 2007).…”
Section: Introductionmentioning
confidence: 99%